(untitled) (Research, Society and Development, 2025)
Objective: To identify the prevalence and factors associated with Primary Bloodstream Infection (BSI) in patients admitted to the Intensive Care Unit (ICU), in addition to verifying the clinical outcome and describing the microbiological profile. Method: Epidemiological, cross-sectional, descriptive, and quantitative study, with retrospective analysis of data collected by the Hospital Infection Control Service (SCIH) between January 2021 and December 2023, through active surveillance. Sociodemographic and clinical data were obtained from electronic medical records, organized and analyzed with Microsoft Excel 2011. Results: The prevalence of BSI was 0.31%, with high mortality (79.49%) and a mean stay of 29.16 days. Men were the most affected (59.02%), with a mean age of 60.9 years. The predominant comorbidities were systemic arterial hypertension (27.49%) and diabetes mellitus (19.61%). The central venous catheter (CVC) was the most commonly used catheter (67.21%), with the jugular vein being the main insertion site (47.06%). Microbiological analysis showed a predominance of Gram-negative microorganisms, with emphasis on Klebsiella pneumoniae (39.34%), Pseudomonas aeruginosa (19.67%) and Acinetobacter baumannii (11.01%). Conclusion: This study provides information on the epidemiological profile of CLABSI in ICUs, highlighting the need to strengthen prevention and control strategies. Identifying the main microorganisms associated with CVC use, as well as their risk factors, can guide specific actions to reduce the prevalence and mortality rate of this infection in critical health care settings.